Regulating the structure of thermoplastic polyurethane elastomers with a diol chain extender to strength performance. Issue 22 (11th April 2023) - Ma, Yao; Wu, Lianfeng; Li, Shaolong; Han, Xu; Peng, Xiaoyong; Feng, Yingmin; Ji, Yumei; Yang, Yike; Liu, Feng
Abstract: The structural defects of thermoplastic polyurethane elastomer (TPU) caused by the uneven distribution of hard segments limiting their potential application in special industrial fields such as aerospace or defense equipment. Optimizing the TPUs' structure is a useful method to adjustable uneven distribution of hard segments and enhance the performance of TPUs. In this work, a chain extender (BMB) embedded in carbamate‐derive units was successfully synthesized by 4, 4′‐diphenylmethane diisocyanate (MDI) and 1, 4‐butanediol (BDO). Using BMB and as chain extender, a modified BMB‐TPU was prepared, and its properties were systematically evaluated. Compared with conventional thermoplastic polyurethane elastomer (BDO‐TPU), BMB‐TPU had a regular structure with uniform hard segments, narrower molecular weight distribution and stronger intra/inter‐chain hydrogen bonding interactions, and thus better microphase separation. The BMB‐TPU exhibited an excellent tensile strength of 35 MPa, 46% higher than 24 MPa for the control BDO‐TPU. Moreover, the heat resistance of BMB‐TPU was also reinforced compared to BDO‐TPU, with an increase of 7.2°C for the degradation temperature of 5% loss and 9.6°C for the viscous flow transition temperature. We believe our paradigm can provide a feasible guide for designing high‐performance TPUs. Abstract : Synthesis schemes for regulating thermoplastic polyurethane elastomers.